War and workers' power in the United States: Labor struggles in war‐provisioning industries, 1993–2016. (20th February 2020) - Payne, Corey R.
Abstract: At the turn of the 21st century, a general disempowerment of industrial workers in the United States yielded pessimistic assessments of the labor movement. Yet, during the height of the wars in Iraq and Afghanistan, industrial war‐provisioning workers in the United States engaged in a wave of largely successful struggles for a greater share of expanding war‐profits. This article investigates these strikes in war‐provisioning industries from 1993 to 2016, finding a wave of offensive struggles between 2003 and 2009. This wave is indicative of an increase in these workers' structural bargaining power, due to growing state reliance on war‐materials provisioning during wartime. Nevertheless, transformations in the organization of production and war‐making made such empowerment ephemeral. This article demonstrates how changes in military actions and strategy—most notably, the wars in Iraq and Afghanistan, the Obama "pivot" to East Asia, and escalating "great power" rivalry—affect the bargaining power of workers in war‐provisioning industries.